Interplay of Chimeric Mating-Type Loci Impairs Fertility Rescue and Accounts for Intra-Strain Variability in Zygosaccharomyces rouxii Interspecies Hybrid ATCC42981 - Bizzarri, Melissa; Cassanelli, Stefano; Bartolini, Laura; Pryszcz, Leszek P.; Dušková, Michala; Sychrová, Hana; Solieri, Lisa (Frontiers in Genetics, 2019)
The pre-whole genome duplication (WGD) Zygosaccharomyces clade comprises several allodiploid strain/species with industrially interesting traits. The salt-tolerant yeast ATCC42981 is a sterile and allodiploid strain which contains two subgenomes, one of them resembling the haploid parental species Z. rouxii. Recently, different mating-type-like (MTL) loci repertoires were reported for ATCC42981 and the Japanese strain JCM22060, which are considered two stocks of the same strain. MTL reconstruction by direct sequencing approach is challenging due to gene redundancy, structure complexities, and allodiploid nature of ATCC42981. Here, DBG2OLC and MaSuRCA hybrid de novo assemblies of ONT and Illumina reads were combined with in vitro long PCR to definitively solve these incongruences. ATCC42981 exhibits several chimeric MTL loci resulting from reciprocal translocation between parental haplotypes and retains two MATa/MATα expression loci, in contrast to MATα in JCM22060. Consistently to these reconstructions, JCM22060, but not ATCC42981, undergoes mating and meiosis. To ascertain whether the damage of one allele at the MAT locus regains the complete sexual cycle in ATCC42981, we removed the MATα expressed locus by gene deletion. The resulting MATa/- hemizygous mutants did not show any evidence of sporulation, as well as of self- and out-crossing fertility, probably because incomplete silencing at the chimeric HMLα cassette masks the loss of heterozygosity at the MAT locus. We also found that MATα deletion switched off a2 transcription, an activator of a-specific genes in pre-WGD species. These findings suggest that regulatory scheme of cell identity needs to be further investigated in Z. rouxii protoploid yeast.